2020
DOI: 10.1002/chem.202000216
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Synthesis of Triphenylphosphine‐Modified Gold Nanoparticles for Synergistic In Vitro and In Vivo Photothermal Chemotherapy

Abstract: Triphenylphosphine (TPP) surface-functionalized and F-108P luronic-stabilized gold nanoparticles (F-108@TPP-AuNPs)h ave been synthesized through ao ne-step approach,l eading to well-defined (9.6 AE 1.6 nm) and watersolublen anoparticles by microwaveh eating an aqueous solution of TPP-Au I Cl in the presence of aP luronic polymer under basic conditions. TPP release was negligible under physiological conditions, bute nhanced significantly at an acidic pH (5.4) mimickingt hat of ac ancerc ell. Laser irradiation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…In another recent study, triphenylphosphine (TPP) surface‐functionalized and F‐108 Pluronic‐stabilized GNPs, presenting a new compound (F‐108@TPP‐AuNPs) with unique properties like water stability, TPP‐controlled release, photostability, high light‐to‐heat conversion capabilities, were proposed. In the in vivo and in vitro trial on Hela cells, this compound, when exposed to irradiation, showed superior anticancer activity through apoptosis mechanism due to the synergism between chemotherapy and hyperthermia with a clear advantage of the combined vs individual therapies [137].…”
Section: Gold Nanoparticlesmentioning
confidence: 99%
“…In another recent study, triphenylphosphine (TPP) surface‐functionalized and F‐108 Pluronic‐stabilized GNPs, presenting a new compound (F‐108@TPP‐AuNPs) with unique properties like water stability, TPP‐controlled release, photostability, high light‐to‐heat conversion capabilities, were proposed. In the in vivo and in vitro trial on Hela cells, this compound, when exposed to irradiation, showed superior anticancer activity through apoptosis mechanism due to the synergism between chemotherapy and hyperthermia with a clear advantage of the combined vs individual therapies [137].…”
Section: Gold Nanoparticlesmentioning
confidence: 99%
“…Indeed, Ag additives to composite coatings on Ti materials have received the bulk of research attention; however, nontoxic and cytocompatible AuNPs, have shown uniquely advantageous broad-spectrum antibacterial activity against both pathogenic Gram-positive and Gram-negative bacteria [101,102]. In the recent past, triphenylphosphine (TPP)-stabilised AuNPs (TPP-AuNPs) have been explored as the precursor material for clinical applications, such as immunolabelling and therapeutics [103][104][105][106][107]. Furthermore, AuNPs stabilised by monosulfonated triphenylphosphine (TPPMS; IUPAC nomenclature: (m-sulfonatophenyl) diphenylphosphane) have been reported to exhibit in vitro antibacterial response.…”
Section: Metal Nanoparticle Coatingsmentioning
confidence: 99%
“…Synthesis of F-108@TPP-AuNPs. Triphenylphosphine (TPP)functionalized and F-108 pluronic polymer-stabilized gold nanoparticles (F-108@TPP-AuNPs) were synthesized according to a previously reported method 48 with some modifications. Briefly, TPP-Au(I)Cl (0.03 mmol) was dissolved and sonicated in a 35-mL vessel with a crimp cap containing 30 mL of 1% F-108 pluronic solution and 90 μL of 1 M NaOH (pH = 10.5).…”
Section: ■ Conclusionmentioning
confidence: 99%